A pintura como modelo para uma filosofia da expressão Maurice Merleau-Ponty - Westphal, Ana Cristina Martins (2015)
This paper aims to clarify the relationship that Merleau-Ponty establishes between painting and philosophy while planning on a reflexive practice "according to" painting procedures. Notably Merleau-Ponty articulates this relationship based on a system of equivalences and relations of analogy whose backgrounds are perception and expression. Although Merleau-Ponty has created a series of metaphorical relations in which painting presents to philosophy as a possible reference -it cannot be affirmed at any given point in time that he seeks to create an aesthetic theory -rather, it is clear that he does not wish to talk "about" painting but "according to" painting. In Eye and Mind Merleau-Ponty works with the idea that a pictorial image is not to be seen from an objectifying relation because the observer does not look at a painting as if looking at an object, the eyes pop out of the head, wander around the painting while it resonates back to these eyes as if it had stemmed from the eyes themselves. This magical vision theory which introduces the idea that vision echoes from the observer‟s interior and makes him believe that the thing is embedded in his flesh appears to Merleau-Ponty through Cézanne‟s painting. The subject is linked to the essence of appearance, to the vision which restores presence, the body and the world. In analogy, Merleau-Ponty confronts the resulting meaning of perception and of spontaneous body gestures to the uniqueness of a work of art. But why does Merleau-Ponty see in painting a model that can serve the purpose of a reflexive practice? In order to answer this question this paper works through the "major subjects" that support Merleau-Ponty‟s reflections such as the Being, the world, the other, the body, returning to conclude with the question above. The starting point is when Merleau-Ponty manifests his desire, that is, to understand the language that begins "in" mankind and not "by" mankind. His assumption is that painting to his eyes becomes the flesh model of such language, that is, he takes painting as the "materialization" of vision inspecting the world 10 instead of a vision that has already a determined meaning system. As an elusive "logic" a "logic" without an exterior model the point in which the eye expresses the first trace of mankind in the world. Merleau-Ponty wishes to demonstrate that there is a first language which precedes a systemic language. A language that does not have its meaning manifested through the relation between word and concept-a sign for a preexisting meaning-but, on the contrary, a language that is created spontaneously amid the intertwining of meaning made transparent through body action. Therefore, it can be stated that meaning is manifested by an invasive relationship [empiétement] and involvement [Ineinander experience] among them. This "language without thought" has its symbolization strength closely related to motion and vision. Vision is the background that supports all of Merleau-Ponty‟s reflection about the origin of meaning: its innateness to [perception], its concerns [things, others, the world], and its results [expression]. The experience of vision makes him question the ways in which to access the visible: the visible, says Merleau-Ponty, rejects its premises when it becomes the outer synthesis. The redesign of the movement of vision appears in his reflection on the clairvoyant-like vision and it retains Cézanne‟s vision at a margin. According to Cézanne, vision is not accepted as a vision from the outside that is presented to him, but as secret genesis of things in the body itself, as an enclosure of the world in the body. The painter, says Cézanne, should not obey the logics of the mind because in it he would be lost and it is with the eyes, assures Cézanne, that the painter must be lost. The eye restores to Cézanne and Merleau-Ponty a feeling of expression of the thing in itself an eye which provides them in the "now" the thing "in the flesh". Like a tidal wave the work of Merleau-Ponty in an act of displacement, it swallows concepts and returns another concept